Backlash As a Counter Assault to Woman’s Progress: Feminism Reading on Habiburrahman El Shirazy’s Novel Cinta Suci Zahrana - Adzhani, Shabrina An (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2022)
This study tries to reveal the backlash contained in Habiburrahman El Shirazy’s novel, Cinta Suci Zahrana. The novel is mostly viewed as promoting feminist values in which the main character is fighting for her dream in education. However, it carries backlash, which is defined as a counter assault toward woman’s progress. In Faludi’s theory, backlash, taking form in myth constructed by patriarchal culture, is used to spread believes that progress women made cause only misery. It is trying to put woman back to inferiority by showing that what they are trying to achieve can make them suffer. This sudy investigates whether the ideas containing backlash appear in Habiburrahman’s Cinta Suci Zahrana. By using qualitative methods and deconstruction reading, this study reveals a discourse that seems to be about women’s struggle, yet carries backlash which takes a form of consequences of the struggle. The result shows that there are backlash ideas taking form as consequences the main character, Zahrana, has to suffer because of her persistence in pursuing her study. Revealing the backlash and how it is presented, this study offers different point of view, not from religious context but limiting the discussion in cultural context. The result is expected to promote critical reading and becomes a contribution to research about backlash.